93 Palliative medicine doctor and paramedic join to form a palliative care rapid response car. A pilot study. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Presswood, Edward; O'Brian, Ed; Hayes, Jo; Baker, Idris; Pease, Nikki
Abstract : Aim: To pilot a palliative medicine doctor and paramedic working together within the community to respond to urgent '999' calls. Is the concept feasible, beneficial to patients and cost effective? Method: Four palliative medicine doctors across South Wales partnered the End of Life Care Lead Paramedic for WAST (EO'B) to form a PCRRC. Potential patients were identified from the list of contemporaneous logged calls for paramedics to respond to. The PCRRC responded to any calls where it seemed likely that it could have a positive impact upon the care of patients. Result: During the four pilot shifts the PCRRC attended four calls and gave telephone advice to three calls. In total 21 hours of doctor time was spent 'on the road'. The anecdotal feedback from the four doctors is mixed. There was not felt to be an overwhelming need for the service but on two occasions it did have an impact upon decision making, including two decisions not to admit patients. The experience improved doctors' insight into paramedic care of patients with palliative care needs. Conclusion: This is a small feasibility study with inherent biases. The PCRRC concept is feasible and can benefit acute clinical decision making but this pilot suggests that it is unlikely to be an efficient use of resources. There are benefits of the PCRRC model for learning, co-ordination of care, and facilitating shared decision making. We are considering other interventions to improve the interaction between palliative care teams and WAST.